The Dynamics of Gender-Based Violence Through Generative Technology (Deepfake & Voice Cloning) in a Digital Communication Perspective - Ilmi Sila Ayu; Febi Ramadhani Rusdin; Muhammad Taslim (Journal of Innovative and Creativity, 2026)
The proliferation of generative Artificial Intelligence (AI) technologies has transformed the digital communication landscape, while simultaneously emerging new variants of online gender-based violence (OGBV). This study aims to analyze how deepfake and voice cloning technologies are utilized as instruments of symbolic terror, blurring the lines between reality and fabrication. Employing a qualitative approach with case study methods and critical discourse analysis, this research examines the phenomenon of AI misuse within the context of Computer-Mediated Communication (CMC). The findings indicate that AI-facilitated violence creates a "hyperreality" of victimization; wherein victims experience tangible psychological and social impacts even though the abusive material is digitally synthesized. From a communication perspective, this phenomenon degrades digital identity integrity and creates a chilling effect that silences women's participation in the public sphere. Indonesian regulations, including the ITE Law and the Sexual Violence Crime Law (UU TPKS), are considered to suffer from a cultural lag in responding to the rapid adoption of this technology.